Race, religion, and the "Indian Muslim" predicament in Singapore - Tschacher, Torsten (Routledge studies on Islam and Muslims in Southeast Asia, 2017)
chapter 1 Introduction -- chapter 2 Histories of a Name: Making the ‘Indian Muslim’ -- chapter 3 Alternatives or ‘Sub-communities’? Engaging with Internal derence -- chapter 4 Dress, Drama, and Divorce: The Clash of Masculinities -- chapter 5 Religion or Culture? Popular Practice and the Perception of derence -- chapter 6 The Markers of derence: History, Language, Identity -- chapter 7 The Organisation of Religious Life -- chapter 8 Representing ‘Indian Muslims’: The Politics of Mediation.